Teologi Belaskasih Allah dalam Puisi “Sepotong Hati Di Angkringan” (2022) Karya Joko Pinurbo - Prihartanti, Marcellina; Andalas, Patricius Mutiara (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2024)
Every human being longs for intimacy with God, receiving His merciful grace. Many of Joko Pinurbo's poems raise the theme of the closeness of human relations. One of Pinurbo's articulate poems voicing social compassion is entitled "A Piece of Heart in Angkringan." However, the theological reading of God's mercy in the poem "A Piece of Heart in Angkringan" has not been explored among professional Indonesian theologians. Pope Francis encouraged pastoral theologians as "influencers of the Gospel" to utilize narrative, aesthetic and digital sources to communicate the Catholic faith to the world. Theological research on this poem can contribute to deepening the theology of God's mercy amidst the challenges of globalization of indifference. Both authors are interested in exploring the theology of God's mercy in the poem "A Piece of Heart in Angkringan" by Joko Pinurbo. How does poet Joko Pinurbo describe God's mercy in the poem "A Piece of Heart in Angkringan?" The two authors want to connect the social compassion implied in the poem "A Piece of Heart in Angkringan" with the theology of God's mercy. This research applies a theological reading method to poetry. The research results show the theological content of God's mercy in the words and metaphors that poet Joko Pinurbo explores in the poem "A Piece of Heart in Angkringan." The poet Joko Pinurbo's poetic exploration aligns with Pope Francis' exploration of the theology of God's mercy: "God is present amid His people, a presence that expresses His compassion and solidarity" (Misericordiae Vultus)AbstrakSetiap manusia merindukan intimitas dengan Allah, menerima rahmat belas kasihan-Nya. Banyak puisi karya Joko Pinurbo mengangkat tema intimitas relasi antarmanusia. Salah satu puisinya yang sangat artikulatif menyuarakan kerahiman sosial berjudul “Sepotong Hati di Angkringan.” Namun, pembacaan teologis atas belaskasih Allah dalam puisi “Sepotong hati di Angkringan” belum mendapatkan eksplorasi di antara teolog profesional Indonesia. Paus Fransiskus mendorong para teolog pastoral sebagai “influencer Injil” untuk memanfaatkan sumber naratif, estetik, dan digital untuk mengkomunikasikan iman Katolik kepada dunia. Penelitian teologis atas puisi ini dapat berkontribusi dalam pendalaman atas teologi belaskasih Allah di tengah tantangan globalisasi ketidakpedulian. Kedua penulis tertarik mengeksplorasi teologi belaskasih Allah yang terkandung puisi “Sepotong Hati di Angkringan”. Bagaimana penyair Joko Pinurbo menggambarkan belaskasih Allah dalam puisi “Sepotong Hati di Angkringan?” Kedua penulis hendak menghubungkan kerahiman sosial yang tersirat dalam puisi “Sepotong Hati di Angkringan” dengan teologi belaskasih Allah. Penelitian ini menerapkan metode pembacaan teologis atas karya sastra puisi. Hasil penelitian menunjukkan kandungan teologi belaskasih Allah dalam kata-kata dan metafor-metafor yang penyair Joko Pinurbo eksplorasi dalam puisi “Sepotong Hati di Angkringan.” Eksplorasi poetik penyair Joko Pinurbo selaras dengan eksplorasi teologi belaskasih Allah oleh Paus Fransiskus bahwa “Allah hadir di tengah-tengah umat-Nya, kehadiran yang menyatakan belarasa dan solidaritas-Nya Nya” (Misericordia Vultus).